Determinants of Labor Productivity in the Artificial Eyelashes Industry - Puji Rakhmawati; Karsinah Karsinah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
This research aims to analyze the labor productivity in the artificial eyelash industry at PT. Royal Korindah in Purbalingga Regency based on the factors that affect. The variables used are labor productivity, education, wages, age, and work experience. The research method used in this research is Multiple Linear Regression Analysis using Eviews9 data processing program. This research used primary data and secondary data. Primary data obtained by the method of interviewing a sample of 100 people labor in the production division at PT. Royal Korindah. Secondary data obtained in the form of publications from various sources. The results showed that education, wages, age, and work experience simultaneously had a positive and significant effect. The factors of education, wages and age have a positive and partially significant effect on labor productivity at PT. Royal Korindah in Purbalingga Regency. In partialy work experience does not have a significant effect on labor productivity at PT. Royal Korindah in Purbalingga Regency.